P29 Impact Of Respiratory Virtual Clinics In Primary Care On Responsible Respiratory Prescribing And Inhaled Corticosteroid Withdrawal In Patients With Copd: A Feasibility Study. (10th November 2014) - d'Ancona, GM; Patel, I; Saleem, A; Royle, F; Hodgkinson, A; Burgess, V; McKenzie, C; Moxham, J; Sethi, T
Abstract : Introduction: There is considerable variation in accuracy of diagnosis and long-term management of COPD in the UK. High rates of inhaled corticosteroid (ICS) prescribing have been reported, raising concerns about their over use, with less focus on high value interventions like stop smoking support/pulmonary rehabilitation. ICS are indicated in severe COPD patients (FEV1 <50% predicted) with frequent exacerbations (>2 per year). Primary care data from SE London showed that 38% of COPD patients were over treated with high dose ICS, resulting in 12 additional cases of pneumonia, and costs >£500, 000, annually. There is limited guidance on methods and feasibility of withdrawing ICS in these patients. Methods: A responsible respiratory prescribing group including CCG medicines management, respiratory pharmacist and integrated respiratory team agreed COPD prescribing guidance across primary/ secondary care. GPs were supported with COPD review templates, written step down protocols and educational events. Virtual clinics with an integrated respiratory consultant/GP respiratory lead were offered to support ICS withdrawal in primary care. Results: 45/48 (94%) of CCG practices took part. Data from 372 patients on COPD registers reviewed over 25 virtual clinics is presented. 321 (86%) patients had confirmed COPD (including 33 with COPD and asthma), 34 had asthma, 15 needed more spirometry and 2 had another diagnosis. 279/321 (87%) patients had a recommendation made: 64 (23%) referred for PR, 53 (19%) for spirometry, and 45 (16%) for smoking cessation. Changes to drug therapies were also recommended: 42 (15%) patients had a LAMA recommended, 16 (5%) a LABA, and while 117/321 COPD patients (37%) required no change to ICS therapy, a graduated step down/stop was suggested for 198 (63%). The outcomes associated with this are in Table 1 . Overall, from Q4 13/14 prescribing data, there was a 4% decrease in high dose ICS (as proportion of total ICS use) resulting in a saving of £50, 000. Conclusion: Integrated working through respiratory virtual clinics offers hugescope to improve high value care for COPD patients. Overuse of ICS in COPD is common and GP-led withdrawal of high dose ICS where appropriate is feasible, acceptable and well tolerated by patients.